2013
DOI: 10.1590/s0104-66322013000300015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reaction operation conditions on the final properties of high impact polystyrene (hips)

Abstract: -The main objective of the present work is to analyze the influence of some important operational reaction parameters (agitation speed, polybutadiene -PB -content and initiator concentration) on the final properties of High Impact Polystyrene (HIPS) produced in bulk. Variable effects are analyzed both qualitatively and quantitatively with the help of a fractional factorial design. Physical, chemical and mechanical properties were evaluated through measurement of the weight-average molecular weight (M w ), poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…When the wt ratio of NR/ST increased from 0.01 (Entry 1) to 0.08 (Entry 2), the amount of HIPS bead in the size of 2.36–4.75 mm increased from 34.3 to 57.8 wt% with decreasing the contents of HIPS with smaller sizes. The previous research reported that the rubber content related to the HIPS bead size since the increase in the rubber content led the higher rates of the particle nucleation and coalescence . Whereas, the reduction of PVA/NR wt ratio from 2.5 (Entry 2) to 1.5 (Entry 3) and AR from 450 (Entry 2) to 350 rpm (Entry 4) increased the amount of HIPS beads with a size of 2.36–4.75 mm from 57.8 to 87.5 wt% and 80.1 wt%, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…When the wt ratio of NR/ST increased from 0.01 (Entry 1) to 0.08 (Entry 2), the amount of HIPS bead in the size of 2.36–4.75 mm increased from 34.3 to 57.8 wt% with decreasing the contents of HIPS with smaller sizes. The previous research reported that the rubber content related to the HIPS bead size since the increase in the rubber content led the higher rates of the particle nucleation and coalescence . Whereas, the reduction of PVA/NR wt ratio from 2.5 (Entry 2) to 1.5 (Entry 3) and AR from 450 (Entry 2) to 350 rpm (Entry 4) increased the amount of HIPS beads with a size of 2.36–4.75 mm from 57.8 to 87.5 wt% and 80.1 wt%, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The effect of AR was claimed as the most important factor. The increase in the agitation rate induced the higher shear rates leading the lower rate of particle coalescence . Moreover, the increase in the PVA concentration hindered the coalescence of the monomer droplet and stabilized the polymer bead leading the reduction of HIPS bead size …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In HIPS-type materials the morphology of the rubber phase is strongly influenced by the reaction conditions such as stirring speed (Cunha et al 2013), initiator (Cunha et al 2013;Laganá et al 2019, Berkenwald et al 2018Chang et al 2012), chain transfer agent (Díaz de León et al 2010), among others, but principally by the nature of the rubber used (Morales et al 2006;Sardelis et al 1987;Wang et al 2019;Li et al 2016;Nazari et al 2018;Hanifpour and Bahri-Laleh 2019). In this context, the influence of the morphology on the mechanical and optical properties of HIPS has been extensively reported in the literature (Aggarwal and Livigni 1977;Anzaldi et al 1994;Katime et al 1995;Wagner and Robeson 1970;Baer 1972;Cigna et al 1976;Silberberg and Han 1978).…”
Section: Introductionmentioning
confidence: 99%